2013
DOI: 10.1016/j.jval.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Validating and Improving the Reliability of the EORTC QLQ-C30 Using a Multidimensional Rasch Model

Abstract: The constructs represented by the multiple-item subscales of the QLQ-C30 were validated. The improved reliability of the multiple-item subscales of the QLQ-C30 under the multidimensional approach can facilitate their applications in clinical and research settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 45 publications
0
35
0
3
Order By: Relevance
“…13 It is a modular questionnaire consisting of a core questionnaire (EORTC QLQ-C30) and additional diagnosis-specific modules. 14 The Spanish version of EORTC QLQ-C30 presented by the EORTC was used for data collection. A sample can be downloaded at the following URL: http://groups.eortc.be/qol/eortc-qlq-c30.…”
Section: Eortc Qlq-c30mentioning
confidence: 99%
“…13 It is a modular questionnaire consisting of a core questionnaire (EORTC QLQ-C30) and additional diagnosis-specific modules. 14 The Spanish version of EORTC QLQ-C30 presented by the EORTC was used for data collection. A sample can be downloaded at the following URL: http://groups.eortc.be/qol/eortc-qlq-c30.…”
Section: Eortc Qlq-c30mentioning
confidence: 99%
“…6 The burden of stroke is greater in Asian countries than in the Western world, including a substantially higher incidence of stroke than myocardial infarction. [7][8][9] However, data on the extent to which several Asia countries have recently fared with regard to improvement in stroke outcomes are relatively sparse. One study suggested the incidence of stroke decreased from 1961 to 2000 in Japan 7 and an overview study revealed that recurrent stroke decreased in each decade from 1960 to 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The validity, reliability, and relevance of these scales for patients with cancer have been clearly demonstrated [78,79] . Examples of assessments in these QoL scales include the ability to perform physical activities; need for help with activities of daily living; extent of symptoms such as pain, fatigue, weakness, gastrointestinal issues, sleep disturbances, sexual dysfunction, and degree of emotional and psychological well-being and their impact on QoL [78][79][80] . Findings from select clinical studies that included assessment of patient QoL are summarized in Table 5 [65,77,[81][82][83][84][85][86] .…”
Section: Patient Qol In Et Studiesmentioning
confidence: 99%